Investigation of the hydraulics of flood flow downstream of the reservoir of Freeport Area of Bataan using HEC-RAS 2D - Caliguid, Paul Timothy D.
The Philippines receives plenty of precipitation and is predicted to receive more due to climate variability. Dam operation in the country is something that is not well managed even with flooding as a risk factor due to dam releases. The Freeport Area of Bataan is an area that can be looked at to analyze possibilities of flooding due to dam operation. This research simulates flooding downstream of the reservoir of the Freeport Area of Bataan for various dam releases and dam breaching scenarios using the 1D-2DHEC-RAS software. A5x5 Digital Elevation Model was used as terrain data and a 1d-2d simulation domain was created over the downstream floodplain area for setting-up the hydraulic model. Calibration and validation were done by simulating observed anecdotal flooding downstream starting from a specific dam gate opening of 0.7 meters. Simulation results revealed a 0.6-meter flood depth in the reported downstream flooding area for a 0.7-meterspillway gate opening. A hypothetical scenario run of 1-meterspillway gate opening per 10-minuterate on the other hand showed flooding in the Freeport Areawith depths reaching up to 1.6minundating about 40 % of the central Freeport floodplain area. Cases of dam overtopping and piping breaching were also simulated. Extreme flooding with depths reaching up to 4.9m and covering the entirety of the floodplain area were observed for a hypothetical dam breach. Mitigation measures such as installation of effective warning system, regular checking of dam structural stability, monitoring of the reservoir and channel water levels, construction of flood walls, dredging of the river channel, and flood proofing of properties, are recommended to mitigate possible flood damage in the Freeport Area due to spillway operations. The use of the numerical model to simulate flooding in this study accentuated the importance of numerical modeling analysis for the design, operation and risk management of downstream reservoir floodplain areas.